2005
DOI: 10.1177/0363546504266484
|View full text |Cite
|
Sign up to set email alerts
|

The Drop-Jump Screening Test

Abstract: The majority of untrained female and male athletes demonstrated a valgus alignment appearance on the video test. After neuromuscular training, female athletes had improved knee separation distances and a more neutral lower limb alignment on landing and takeoff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(90 citation statements)
references
References 27 publications
3
85
1
Order By: Relevance
“…were similar to values previously reported by other investigators [36,37] who evaluated knee injury predisposition, finding greater risk for knee injury in women when compared to their male counterparts. Previous investigators have reported that double-legged landing dynamic knee valgus measures of 4.15 cm [37] and 5 cm [36] predispose females to injuries when compared to their male counterparts. Therefore, we hypothesize that both groups exhibited landing mechanics that may predispose them to knee injuries given that our dynamic knee valgus values during the double-legged drop jump were 4.17 ± 2.32 cm and 6.24 ± 3.71 cm for the control and SG-ACLr groups, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…were similar to values previously reported by other investigators [36,37] who evaluated knee injury predisposition, finding greater risk for knee injury in women when compared to their male counterparts. Previous investigators have reported that double-legged landing dynamic knee valgus measures of 4.15 cm [37] and 5 cm [36] predispose females to injuries when compared to their male counterparts. Therefore, we hypothesize that both groups exhibited landing mechanics that may predispose them to knee injuries given that our dynamic knee valgus values during the double-legged drop jump were 4.17 ± 2.32 cm and 6.24 ± 3.71 cm for the control and SG-ACLr groups, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…The analysis reports hip, knee, and ankle separation distances, along with maximum vertical jump height. Test-retest reliability for measures recorded in this manner have been reported as very high, ICC Ͼ 0.90 (20). Anthropometric data including age (years), height (cm) and mass (kg) also were collected at the time of preand posttesting.…”
Section: Methodsmentioning
confidence: 99%
“…McLean et al25 also indicated that being able to identify specifically at-risk individuals during their initial ground contact would allow greater opportunities to intervene with these individuals versus interventions in which some people may not need the training. In 2005, Noyes et al26 sought to develop a simple videographic test that would measure the distance between the hips, knees, and ankles in the coronal plane. They used the drop-jump screening test to assess gender and neuromuscular training differences in female athletes.…”
mentioning
confidence: 99%